Spirituality and resilience in home care - Zandavalli, Rafaela Brugalli (2020)
To evaluate the relationship between religiosity and spirituality with resilience in HC patients from Primary Health Care Units (PHC-U) of Porto Alegre (RS), Brazil. Methods: Cross-sectional and descriptive quantitative study including 44 adults from four PHC-U in HC due to chronic conditions and controlled/compensated health problems with some dependence on activities of daily living. We used religiousness (DUREL), spirituality (ARES), resilience (RS-14), functionality (Katz), depressive symptoms (PHQ-2), social support (mMOS-SS), economic classification (ABEP 2016) and severity of clinical conditions (CIRS-G) scales. Results: Most of the evaluated patients were female (72.7%), elderly (average 74 years), widows, white, low socioeconomic status, low education, retired, with an average time of 7.5 years of home restriction and with moderated degree of resilience. Respondents have high religiosity and spirituality rates, with 90.9% presenting high intrinsic religiosity and 79.6% performing private religious practices one or more times a day. Most (88.6%) consider important that their religiosity and spirituality is addressed in their health care, but only 20.5% have been asked about it. Resilience was associated with higher spirituality (B=0,44; p=0,02), controlling this effect for social support and depressive symptoms; and older age (B=0,18; p=0,02). Conclusion: The study corroborates the relevance of the religiosity and spirituality dimension and indicates its role in promoting resilience in this population in HC. The approach to religiosity and spirituality with these individuals is recommended, strengthening the integral care recommended by PHC.